(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
In Quindío, on December 24, 25, and 26 in 1999 there were some mud flows that affected the village La Virginia. These events were associated with the hillsides instability caused by the earthquake on January of 1999 and several rains on December. In the last ten years the phenomenon has been documented well enough to propose intervention actions supported in the detailed analysis of the variables that get involved there. University of Quindío, through Extension Office of Faculty of Engineering and with support of research groups CIDERA and QUIMBAYA, decided to analyze this phenomenon integrating environmental, geological, seismic, geotechnical, hydrologic and hydraulic conditions to define the impact that a phenomenon of mass removal would cause to La Virginia. The analysis was carried out with ArcGIS 9.3 and FLO-2D to generate risk and mud flood hazard maps, respectively.